Detection of Antinuclear Antibody in Childhood Rheumatic Diseases by Immunofluorescence Assay and Enzyme Immuno Assay - Dipti, Tanjeem Rabika; Azam, Mohammad Shaiful; Sattar, Mohammad Humayun; Rahman, Shahana (Bangladesh Journal of Child Health, 2012)
Background: Anti-nuclear antibodies (ANAs) are specific antibodies directed against a variety of nuclear antigens. Indirect immunofluorecence (ANA-IFA) and Enzyme Immunoassay (ANA-EIA) are commonly used methods for ANA detection. The positivity of ANA-IFA using HEp-2 cell substrate is 90-100% in systemic rheumatic diseases. On the other hand positivity of ANA-EIA is found to be much lower in different studies. In Bangladesh most of the laboratories use ANA-EIA method. Objectives: To detect ANA by Immunofluorecence Assay (using HEp-2 cell substrate) and Enzyme Immuno Assay in childhood rheumatic diseases and to compare ANA positivity by these two methods. Materials and methods: Cross sectional comparative study. Total 40 patients of different childhood rheumatic diseases were enrolled in this study. Serum sample was collected and tested for detection of ANA by Immunofluorecence Assay using HEp-2 cell substrate and Enzyme Immuno Assay. Result: Among total 40 cases, 67.5% were ANA positive by IFA method and 27.5% were ANA positive by EIA method. Conclusion: ANA-IFA is superior to ANA-EIA for detection of ANA in childhood rheumatic diseases. DOI: http://dx.doi.org/10.3329/bjch.v35i2.10355 Bangladesh J Child Health 2011; Vol 35 (2): 49-52